Let the vertex of the parabola be (x0, y0). As the latus rectum is 1, a = 1/4. The equation of the parabola is (y - y0)^2 = (x - x0)

It passes through (3,1) and (-5,5)

=> (5 - y0)^2 = (- 5 - x0) and (1 - y0)^2...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Let the vertex of the parabola be (x0, y0). As the latus rectum is 1, a = 1/4. The equation of the parabola is (y - y0)^2 = (x - x0)

It passes through (3,1) and (-5,5)

=> (5 - y0)^2 = (- 5 - x0) and (1 - y0)^2 = ( 3 - x0)

x0 = -5 - (5 - y0)^2

substituting in (1 - y0)^2 = ( 3 - x0)

=> (1 - y0)^2 = 3 + 5 + (5 - y0)^2

=> (1 - y0)^2 - (5 - y0)^2 = 8

=> (1- y0 - 5 + y0)(1 - y0 + 5 - y0) = 8

=> -4*(6 - 2*y0) = 8

=> 2y0 - 6 = 2

=> 2y0 = 8

=> y0 = 4

x0 = -5 - (5 - y0)^2

=> x0 = -5 - ( 5 - 4)^2

=> x0 = -5 - 1

=> x0 = -6

**The equation of the parabola is (y - 4)^2 = x + 6**